A crisis within crisis in Pakistan: The IDP's of Swat and Buner Districts - Malik, Sohail Jehangir (2009)
Sohail Jehangir Malik, Chairman, Innovative Development Strategies (Pvt.) Ltd 12th August, International Food Policy Research Institute (IFPRI), Washington D.C.